Case report: The safety of laparoscopic surgery for the retroperitoneal bronchogenic cyst - Li, Hancong; Xu, Jun; Feng, Qingbo; Cai, Zhaolun; Li, Jiaxin (Frontiers in Oncology, 2022)
Introduction: Bronchogenic cyst is a congenital aberration of bronchopulmonary malformation with bronchial-type, pseudostratified cylindrical epithelium. They are usually discovered in the mediastinum and intrapulmonary but rarely encountered in retroperitoneum. We report a case of retroperitoneal bronchogenic cyst and perform a literature review to summarize the safety of laparoscopic resection for this rare disease. Case Presentation: We report a 57-year-old woman who was admitted to our hospital with no clinical symptoms and was found by chance to have masses in the adrenal gland area during routine physical examination. An abdominal CT examination revealed a cystic lesion was found in the left suprarenal region. Afterward, the patient underwent a laparoscopic exploration. Histopathological findings confirmed the diagnosis of retroperitoneal bronchogenic cyst. The patient recovered uneventfully without signs of recurrence during a 1-year follow-up period. Conclusion: Bronchogenic cyst is rare in the retroperitoneal region. It should be considered as one of the differential diagnoses of a retroperitoneal neoplasm, especially in the left retroperitoneal region. Laparoscopic surgery is technically feasible and safe for the treatment of patients with a retroperitoneal bronchogenic cyst.